Granitoides peraluminosos y su relación con las rocas fuentes - Dahlquist, Juan Andrés (2005)
Comparative compositional studies between two peraluminous unit with magmatic andalucite and cordierite indicate that they were produced by partial melting of two differents metasedimentary source rocks. We conclude that geochemical studies from peraluminous unit contributes to define the source rocks and to constrain the pre-orogenic geotectonic environment .